2020
DOI: 10.1177/1753193419899037
|View full text |Cite
|
Sign up to set email alerts
|

Limb preserving surgery for soft-tissue sarcoma in the hand: a retrospective study of 51 cases

Abstract: Our retrospective study analysed the long-term results of a conservative limb-preserving surgical strategy in 51 patients with soft-tissue sarcoma of the hand from a single institution. We assessed survival and prognostic factors, including the surgical margins. No transradial amputations were performed. Microscopically free resection margins were obtained in 45 of the patients. The remaining six patients had microscopically incomplete resection. Forty-four surviving patients had a median follow-up of 6.5 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
(25 reference statements)
0
1
0
Order By: Relevance
“…Historically, the amputation of the extremity was state of the art in the treatment of sarcomas of the upper and lower extremities. Through the years, it was shown that the amputation of the extremity is not advantageous regarding long-term survival compared to R0 resection [ 22 , 23 , 24 ]. Important is the so-called wide resection in the healthy tissue surrounding the tumor with tumor free margins [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Historically, the amputation of the extremity was state of the art in the treatment of sarcomas of the upper and lower extremities. Through the years, it was shown that the amputation of the extremity is not advantageous regarding long-term survival compared to R0 resection [ 22 , 23 , 24 ]. Important is the so-called wide resection in the healthy tissue surrounding the tumor with tumor free margins [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 99%